Shades of humanity: state sovereignty and humanitarian principles in the Syrian civil war - Ümit Seven (Journal of International Humanitarian Action)
Abstract In the Syrian civil war, the Syrian government has imposed numerous restrictions and employed violence to assert its sovereignty in humanitarian action, creating significant challenges for humanitarian aid organizations. These organizations, in turn, have had to navigate a complex landscape, contending with political realities that often subordinate humanitarian principles to the primacy of state sovereignty. This research examines this interaction between the state and aid organizations in the provision of humanitarian assistance, focusing on how aid organizations interpret and experience state sovereignty in their work. Based on a survey conducted with aid professionals, I first identify the ways state sovereignty is articulated in humanitarian action and then explore aid workers’ perceptions of state sovereignty in relation to humanitarian norms and principles. I demonstrate that the global governance aimed at preserving human lives and mitigating suffering, far from being singular and cohesive, is marked by diversity and shaped by the influence of state sovereignty. While the overarching objective remains consistent—to alleviate human suffering—the very bedrock of international humanitarian norms and principles amidst the conflict constantly undergo negotiation and divergence across humanitarian aid organizations.